2013
DOI: 10.1371/journal.pone.0082746
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Brain Metabolite Concentrations: An In Vivo Magnetic Resonance Spectroscopy Study with a Clinical MR System at 3 Tesla

Abstract: Brain metabolite concentrations change dynamically throughout development, especially during early childhood. The purpose of this study was to investigate the brain metabolite concentrations of neonates (postconceptional age (PCA): 30 to 43 weeks) using single-voxel magnetic resonance spectroscopy (MRS) and to discuss the relationships between the changes in the concentrations of such metabolites and brain development during the neonatal period. A total of 83 neonatal subjects were included using the following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 36 publications
4
31
0
Order By: Relevance
“…Most metabolite concentrations were similar to those previously reported by others despite differences in methodology as summarized in Table (Kreis et al, ; Pouwels and Frahm, ; Pouwels et al, ; Sarchielli et al, ; Horska et al, ; Schubert et al, ; Minati et al, ; Tomiyasu et al, ).…”
Section: Resultssupporting
confidence: 87%
“…Most metabolite concentrations were similar to those previously reported by others despite differences in methodology as summarized in Table (Kreis et al, ; Pouwels and Frahm, ; Pouwels et al, ; Sarchielli et al, ; Horska et al, ; Schubert et al, ; Minati et al, ; Tomiyasu et al, ).…”
Section: Resultssupporting
confidence: 87%
“…This represents a more accurate estimation of the absolute metabolite concentrations otherwise underestimated if this correction is not used. 25 Inherent limitations with metabolite ratios and misconceptions that they self-correct for type of scanner, localization method differences, gain instabilities, regional susceptibility variations, and partial volume effects are addressed using absolute metabolite concentrations in addition to ratios.…”
Section: Discussionmentioning
confidence: 99%
“…23 This was set in the LCModel parameter "WCONC" rather than 35,880 mmol/L used as the default value for white matter, which underestimates the absolute metabolite concentrations. 24,25 Based on the LCModel output, MR spectra with line width at full width at half maximum of Ͼ0.1 ppm (approximately 6 Hz) and/or SNR of Ͻ3 were excluded. Metabolite concentrations with a confidence level of the Cramer-Rao lower bounds 26 of Ͼ20% were also excluded from the subsequent analysis.…”
Section: Mr Spectroscopy Processingmentioning
confidence: 99%
“…It is now established that metabolites can be predetermined by adverse conditions before birth during early development and which play an important role in prevention of disease at adult. Several studies had reported the metabolites changes in fetuses and child (Tomiyasu et al, 2013) or rat embryos (Akimova et al, 2017). Sato, Tomonaga, Denbow, and Furuse (2009) reported the changes of amino acids during embryonic development in broiler chickens.…”
Section: Introductionmentioning
confidence: 99%